KONFLIK BISNIS EKSPOR PASIR LAUT BERDASARKAN UNDANG-UNDANG NOMOR 27 TAHUN 2007 DAN PERATURAN PEMERINTAH NOMOR 26 TAHUN 2023 - Maritza, Allya Lavenia; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
Conflicts between economic interests have become a controversial issue in the utilization of sea sand, which has high demand in the international construction sector but has the potential to damage the ecosystem and threaten the welfare of the community. The Indonesian government previously issued Law Number 27 of 2007 to protect the ecosystem of coastal areas and small islands from over-exploitation. However, the ratification of Government Regulation Number 26 of 2023 which reopens sea sand exports has sparked controversy. This new policy is considered to prioritize short-term economic interests and ignore long-term environmental and social impacts. With a normative approach, this study examines the applicable regulations and applies the theory of legal certainty to analyze the impact of the policy. It was found that this decision reflects a conflict of business interests and has the potential to ignore the community, damage the ecosystem, and violate the principle of sustainability. The conclusion of this study shows that there is legal uncertainty due to the lack of regulatory consistency, so that regulatory harmonization is needed to achieve fair and sustainable natural resource governance. Keywords: Business Conflict, Sea Sand Export, Legal Certainty